2018
DOI: 10.3389/fncel.2018.00451
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Exacerbation of Neuroinflammatory Response After a Combined Therapy in Old Parkinsonian Mice

Abstract: The design of therapeutic strategies that focus on the repositioning of anti-inflammatory and antioxidant drugs are a great bet to slow down the progression of neurodegenerative disorders. Despite the fact that Parkinson’s disease (PD) is an age-related pathology, almost all experimental studies are carried out in young animals. Here, we evaluated the possible neuroprotective effect of the combination of the antioxidant N-acetylcysteine (NAC) and the anti-inflammatory HA-1077 in aged 1-methyl-4-phenyl-1,2,3,6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In each slice, four images per hemisphere and striatal area were taken at 20× magnification. Quantification of the TH immunoreactivity in striatal fibers was assessed by optical density using Fiji software, applying a plug-in for color deconvolution for DAB stainings [ 9 , 67 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each slice, four images per hemisphere and striatal area were taken at 20× magnification. Quantification of the TH immunoreactivity in striatal fibers was assessed by optical density using Fiji software, applying a plug-in for color deconvolution for DAB stainings [ 9 , 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Once inside the cell, MPP+ induces the disruption of the mitochondrial electron chain, which triggers oxidative stress and neurotoxic effects, with neuronal death as a result [ 8 ]. Additionally, several studies have shown that MPTP also induces an exacerbated inflammatory response, which has been shown to be a key element in neurodegeneration [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the results obtained here in glial cells substantiate the hypothesis first suggested by Thomas and colleagues [55] on a role for microglial and astroglial activation in the neurotoxicity mediated by amphetamine-related drugs. Thus, several studies have demonstrated that astroglial and microglial activation may sustain neurodegeneration in the dopaminergic nigrostriatal system [56], and this mechanism has also been proposed to participate in the neurotoxic dopaminergic damage induced by MDMA [30].…”
Section: Tablementioning
confidence: 99%
“…However, intraperitoneal treatment for 14 days with zonisamide, an antiepileptic agent that was shown to improve PD symptoms in clinical trials [80], has been demonstrated to be accompanied by increased astrocytic S100B levels in the basal ganglia of 6-OHDAtreated mice [81]. The combined treatment of the antioxidant N-acetylcysteine and the anti-inflammatory agent HA-1077 has been associated with enhanced dopaminergic death and astrocytic activation accompanied by elevated S100B expression in MPTP-treated mice [82]. Therefore, treatment approaches against PD may diversely affect S100B levels, probably depending on the specific molecular processes underlying each therapeutic strategy.…”
Section: S100b As a Potential Therapeutic Target Against Pdmentioning
confidence: 99%